Unemployment and crime: Experimental evidence of the causal effects of intensified ALMPs on crime rates among unemployed individuals - Andersen, Signe Hald (The British journal of criminology, 2021)
Previous studies investigate whether levels of welfare benefits reduce crime among the unemployed. The current paper expands this literature by testing whether the intensity of other welfare programs aimed at the unemployed affects their criminal activity. For this purpose, the study uses evidence from a Danish social experiment that randomly assigned active labour market programs (ALMPs) of different intensity to newly unemployed individuals (N = 4.710, 41.7 per cent women). Using a negative binomial model, I find that the experiment significantly reduced the number of criminal convictions from 61 in the control group to 43 among the treated. While this 40 per cent decrease reflects a numerically small effect, the results still indicate that the intensity of ALMPs affects criminal behaviour among the unemployed.